Practical Guidelines Management of Graves Ophthalmopathy - Imam Subekti; Pradana Soewondo; Suharko Soebardi; Budiman Darmowidjojo; Dante Saksono Harbuwono; Dyah Purnamasari; Tri Juli Edi Tarigan; Wismandari Wisnu; Dicky Levenus Tahapary; Farid Kurniawan; M Sidik; Syntia Nusanti; et al. (Acta Medica Indonesiana, 2020)
Graves’ ophthalmopathy is the most common extra-thyroid manifestation in patients with Graves’ disease, based on inflammatory and autoimmune conditions in orbital tissue. This practical guideline was formed by a multidiciplinary team, and is intended to provide guidance for diagnosis and management of Graves’ ophthalmopathy in daily clinical practice to improve quality of care and treatment outcome.